Oral and general health-related quality of life in oral squamous cell carcinoma patients- comparative analysis of different treatment regims - Shailesh M. Gondivkar; Amol R. Gadbail; Sachin C. Sarode; Amol Hedaoo; Subhrajit Dasgupta; Balkrishna Sharma; Aparna Sharma; Rima S. Gondivkar; Monal Yuwanati; Shankargouda Patil; Rahul N. Gaikwad (Journal of Oral Biology and Craniofacial Research)
Background: Modern aggressive oncological treatment options for oral squamous cell carcinoma (OSCC) are inevitably associated with impaired general health-related quality of life (HRQoL) and oral HRQoL (OHRQoL). However, there is dire need for prospective and concomitant assessment of HRQoL and OHRQoL after different treatment regims. Hence, present study was designed to investigate HRQoL and OHRQoL in patients treated for OSCC using various modalities. Methods: 135 OSCC patients were grouped according to treatment rendered into Group A: surgery only; Group B: post-surgical radiotherapy (PRT); and Group C: post-surgical chemo-radiation (PCRT). The 12-item Short Form Health Survey (SF-12) and Oral Health Impact Profile-14 (OHIP-14) were intervened to assess HRQoL and OHRQoL respectively at 1-month and 6-months post-treatment. Results: At 1-month post-treatment, patients who received PCRT showed significantly lower mean values for physical and mental domains of SF-12 and higher mean subscales and overall OHIP-14 (24.57 ​± ​2.62) score than those treated by surgery alone (10.55 ​± ​2.26) and PRT (20.20 ​± ​3.80), with largest differences between PCRT and surgery alone groups (p ​< ​0.001). Social functioning, general health and bodily pain of SF-12 and functional limitations, physical pain and physical disability amongst OHIP-14 domains were greatly affected. Although few physical domains of SF-12 showed significant improvement, mental domains remained a greater problem after 6 months. However, OHRQoL was significantly poor in all the three study groups (p ​< ​0.001). Conclusion: Irrespective of the post-treatment duration, patients who received PCRT had worse HRQoL and OHRQoL. There is a need to identify factors associated with impaired HRQoL and OHRQoL to customize better therapeutic decisions.